Mental health considerations for children & adolescents in COVID-19 Pandemic - Imran, Nazish (Pak J Med Sci, 2020)
Children are not indifferent to the significant psychological impact of the COVID-19 Pandemic. They experience fears, uncertainties, substantial changes to their routines, physical and social isolation alongside high level of parental stress. Understanding their emotions and responses is essential to properly address their needs during this pandemic. In this article, we highlight children’s vulnerability, provide an overview of common symptoms of distress in different age groups, and summarize the interventions and resources available to promote child mental health and wellbeing during these challenging times. We advocate that prioritizing mental health including child & adolescent mental health is an essential component of any universal, community led response to COVID-19 Pandemic.